Financial Performance of Bank NTB Syariah: Before and After Becoming an Islamic Commercial Bank - Mainata, Dedy; Pratiwi, Angrum; Hasanah, Mauizatul (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This study evaluates the financial performance of Bank NTB Syariah before and after its conversion into an Islamic Commercial Bank (BUS) in 2018. The conversion aimed to foster more equitable economic growth and improve the overall status of the NTB community. Utilizing Financial Ratio Analysis (FRA), this research examines various financial ratios, including ROA, ROE, NIM, NPF, BOPO, FAR, FDR, ELR, EAR, CAR, DER, and DAR, to assess performance differences pre- and post-conversion. The findings indicate significant improvements in key financial indicators such as ROA, ROE, NIM, NPF Net, and BOPO after the conversion, demonstrating enhanced profitability and efficiency. However, there were no notable changes in the ratios of FAR, FDR, ELR, EAR, CAR, DER, DAR, and NPF Gross, suggesting stability in these areas. This comprehensive analysis highlights the positive impact of the conversion on Bank NTB Syariah's financial performance and provides valuable insights for investors, bank managers, and policymakers regarding the benefits of converting to an Islamic Commercial Bank. The study's findings underscore the importance of strategic structural changes in enhancing the financial health and operational efficiency of financial institutions.